Uranium in groundwater in parts of India and world: A comprehensive review of sources, impact to the environment and human health, analytical techniques, and mitigation technologies - Balaram, V.; Rani, A.; Rathore, D.P.S. (Geosystems and geoenvironment, 2022)
•A comprehensive evaluation on various aspects of uranium in groundwater.•Detection and determination of elemental and isotopic concentrations of uranium in water.•Currently available remediation technologies for the removal of uranium from water. Uranium concentration/contamination in groundwater is currently a subject of concern all over the world due to related severe health problems to humans, as groundwater is the main drinking water source in rural and urban India and also in several parts of the world. Uranium concentration in groundwater in shallow aquifers in various states such as Punjab, Rajasthan, Karnataka Telangana, and Madhya Pradesh of India varies from 0 to 1443 ng/ml exceeding the permissible levels by WHO for drinking water (30 ng/ml), at several places. Very high concentrations ranging up to 1400 ng/ml were reported in some areas in other countries such as Canada, the USA, Mongolia, Burundi, Zambia, Nigeria, South Korea, Pakistan, Jordon, Afghanistan, China, and Myanmar. Various natural aspects which influence the uranium concentration in groundwater such as bedrock geology, water chemistry, and redox conditions, and anthropogenic sources such as mining activities (uranium, coal, and phosphate rock), nuclear activities, agricultural practices of using phosphate fertilizers, and prevalence of excessive nitrate in some areas, are described with examples. Some of the important analytical techniques for the precise and accurate determination of elemental and isotopic concentrations of uranium in water samples, such as LED fluorimetry, Raman spectroscopy, inductively coupled plasma mass spectrometry (ICP-MS), high-resolution ICP-MS (HR-ICP-MS), and multi-collector ICP-MS (MC-ICP-MS), are described. A number of advancements have taken place in remediation technologies for the removal of uranium in drinking water using different physical, chemical, and biological methods including rainwater harvesting. Various mitigation strategies for the effective removal of uranium from water during treatment, such as bioremediation using biochars from different sources, nanoparticle technology, and adsorption by magnesium (Mg)-iron (Fe)-based hydrotalcite-like compounds (MF-HT), are described in detail. [Display omitted]